Strategi Customer Relationship Management Terhadap Kepuasan Dan Loyalitas Pada Pelanggan Justicia Veronica Coffee Di Setia Budi Medan - Junior Lumban Gaol; Indahwati Lestari; Finta Aramita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The tight competition in the food and beverage industry makes companies like Justicia Veronica Coffee need to focus on long-term relationships with customers. Among various strategies, Customer Relationship Management (CRM) is the most popular strategy in managing customer relationships. The Influence of Customer Relationship Management Strategy on Satisfaction and Loyalty in Justicia Veronica Coffee Customers the Setia Budi Medan Outlet). This study aims to determine the influence of the Customer Relationship Management Strategy on Customer Satisfaction and Loyalty in Justicia Veronica Coffee customers. This study uses a quantitative research design with data collected through questionnaires, involving a sample of 135 respondents who have previously at the Justicia Veronica Coffee Setia Budi Medan outlet. The data were processed using SPSS 27, and the analytical techniques applied include linear regression analysis, t-test (partial), F-test (simultaneous) and Analisys path. The research results show: (1) The Customer Relationship Management Strategy significantly influences customer satisfaction (2) The Customer Relationship Management Strategy significantly influences customer loyalty (3) Customer satisfaction significantly influences customer loyalty (4) The Customer Relationship Management Strategy and Customer Satisfaction simultaneously have a positive influence on Customer Loyalty.